2018
DOI: 10.1002/jbm4.10037
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐Phosphate Modulates the Effect of Estrogen in Human Osteoblasts

Abstract: Production of sphingosine-1-phosphate (S1P) is linked to 17β-estradiol (E2) activity in many estrogen-responsive cells; in bone development, the role of S1P is unclear. We studied effects of S1P on proliferation and differentiation of human osteoblasts (hOB). Ten nM E2, 1 μM S1P, or 1 μM of the S1P receptor 1 (S1PR1) agonist SEW2871 increased hOB proliferation at 24 hours. S1PR 1, 2, and 3 mRNAs are expressed by hOB but not S1PR4 or S1PR5. Expression of S1PR2 was increased at 7 and 14 days of differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…These results corroborate our previous study that implicated SKs in the mineralization capacity of osteoblasts and chondrocytes . In accordance, the addition of exogenous S1P to human osteoblasts (hOB CC‐2538) has been shown to enhance Bglap2 and Alpl gene expression . These effects on osteoblast differentiation are in addition to those already observed on their proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate our previous study that implicated SKs in the mineralization capacity of osteoblasts and chondrocytes . In accordance, the addition of exogenous S1P to human osteoblasts (hOB CC‐2538) has been shown to enhance Bglap2 and Alpl gene expression . These effects on osteoblast differentiation are in addition to those already observed on their proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…(19) In accordance, the addition of exogenous S1P to human osteoblasts (hOB CC-2538) has been shown to enhance Bglap2 and Alpl gene expression. (48) These effects on osteoblast differentiation are in addition to those already observed on their proliferation. Further, S1P can indeed stimulate the proliferation of rat, bovine, and human primary chondrocytes.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, the formation of S1P can be modulated by treatments targeting SPHK. Using SKi (10 μmol/L), a SPHK inhibitor, in hOB assays further confirmed this hypothesis 49 . Because these enzymes have limited distribution and their activation can be easily controlled, controlling the S1P concentration by regulating enzyme activation has tissue specificity, and they have great advantages over directly regulating S1PRs.…”
Section: The Effect Of S1p On Osteoporosismentioning
confidence: 64%
“…Various in vitro studies revealed that S1P controls bone formation by regulating OB proliferation and survival. 48 52 Dziak et al were one of the first to demonstrate that short-term incubation with S1P leads enhances proliferation rate in primary human osteoblastic cells, as well as in the human osteosarcoma cell lines MG63 and G292, in a pertussis toxin-sensitive manner. Therefore, the researchers suggested the involvement of S1PR1.…”
Section: S1p As An Osteoclast–osteoblast Coupling Factormentioning
confidence: 99%